Evaluation of wear and corrosion resistances of laser cladding TaC/TiC/Stellite X-40 Co-based composite coatings on copper surface. (29th July 2022) - Zhu, Guangyu; Yan, Hua; Li, Zhiyuan; Zhang, Peilei; Yu, Zhishui; Lu, Qinghua; Guo, Jialong
ABSTRACT: The TaC/TiC/Stellite X-40 Co-based composite coatings with different contents were successfully cladded on a Cr-Zr-Cu alloy substrate. The microstructure, wear and corrosion resistance of the composite coatings were investigated by means of X-ray diffraction (XRD), optical microscope (OM), energy dispersive spectrometer (EDS), scanning electron microscope (SEM), sliding wear test, as well as corrosion test in 3.5% NaCl solution. The results showed that Ta and Ti atoms easily form Co3Ta and Co3Ti hard phases with Co to increasing the hardness of the coating. Compared with the substrate, the wear resistance, corrosion resistance and hardness of the composite coatings were significantly improved. The wear resistance of the 20 wt. % TaC and 10 wt. % TiC composite coatings were better than that of the substrate. When the TaC content was 20 wt. % and the TiC content was 15 wt. %, the coating with excellent corrosion resistance (-0.153V).